Optimization of high power and high efficiency operation of 77GHz gyrotrons for ECRH in the large helical device - Shimozuma, T; Takahashi, H; Ito, S; Kobayashi, S; Kubo, S; Yoshimura, Y; Igami, H; Nishiura, M; Ogasawara, S; Makino, R; Mizuno, Y; Okada, K; et al. (2011)
Three Mega-Watt 77GHz gyrotrons were developed for an ECRH system in LHD. Their operation could be highly optimized by means of two-step rise of an anode voltage. Output power of 1.78MW with 37.9% efficiency were obtained in the 3rd gyrotron. The system improvement has been promoted including the development of a mmw-beam position and profile monitor. © 2011 IEEE.